Sifat Perekatan Kayu Randu Yang Distabilkan Dengan PEG-1000 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACTRandu wood is still neglected due to some unwanted wood properties, especially wood stability and drying defects. Its wood is light, yellow brownish color appearance and hopely could replace other light commercial woods. To improve its wood quality, a PEG-1000 chemical treatment was chosen. Two factors, namely PEG-1000 concentration and axial position were employed in wood adhesion factorial experiment arranged in Completely Randomized Design, with three replication. Tukey treatment mean separation was followed. Results showed that both factors significantly influenced adhesion properties. Their effects in all wood adhesion parameters are individual. No interaction effect of PEG concentration and axial position emerged. Dry and wet adhesion strength of PEG treated plywood were 41 and 10,8 kg/cm2, while untreated plywood strength were 12,4 and 10,0 kg/cm" respectively. Higher PEG concentration produced lower adhesion strength. PEG treated wood showed 54-74% better dimensional stability, but it increased wood moisture equilibrium content.